2019
DOI: 10.1186/s12879-019-4569-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis in HIV-infected adults on first- and second-line antiretroviral therapy in India

Abstract: BackgroundProgrammatic data on the baseline risk of tuberculosis in people living with HIV (PLHIV) are needed to evaluate long-term effectiveness of the ongoing isoniazid preventive therapy (IPT) roll-out in India.MethodsWe estimated the incidence rate and risk factors of tuberculosis disease in adult PLHIV initiating first- and second-line anti-retroviral therapy (ART) prior to widespread IPT in a public ART center in Pune, India.Results4067 participants contributing 5205.7 person-years of follow-up on first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
4
3
0
Order By: Relevance
“…Subgroup analysis by study population of the current study showed that the pooled TB incidence among adults and children was slightly different which were 5.01 (95% CI 3.51, 6.50) and 4.34 (95% CI 2.96, 5.71) respectively. This finding was consistent with studies done in India in 2019 and Tanzania in 2015 which were 4.39 cases and 4.4 cases per 100 PYO, respectively [ 27 , 28 ]. This might be the same socioeconomic status between these countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subgroup analysis by study population of the current study showed that the pooled TB incidence among adults and children was slightly different which were 5.01 (95% CI 3.51, 6.50) and 4.34 (95% CI 2.96, 5.71) respectively. This finding was consistent with studies done in India in 2019 and Tanzania in 2015 which were 4.39 cases and 4.4 cases per 100 PYO, respectively [ 27 , 28 ]. This might be the same socioeconomic status between these countries.…”
Section: Discussionsupporting
confidence: 92%
“…The current study revealed that the pooled TB incidence among HIV-infected patients after initiation of ART was 4.76 (95% CI 3.69–5.83) per 100 PYO which was in line with the primary studies done in India in 2019 and Tanzania in 2015 which were 4.39 cases and 4.4 cases per 100 PYO, respectively [ 27 , 28 ]. The current finding of pooled incidence was higher than studies conducted in higher-income countries in 2012, Asia in 2019, Brazil and Nigeria in 2017, and South Africa in 2005 which were 0.3, 0.99, 1.90, 0.57, and 2.44 per 100 person-years, respectively [ 29 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…Subgroup analysis by study population of this study showed that the pooled TB incidence among adults and children was slightly different which were 5.01 (95% CI: 3.51, 6.50) and 4.34 (95% CI 2.96, 5.71) respectively. This finding was consistent with studies done in India in 2019, and Tanzania in 2015 which were 4.39 cases, and 4.4 cases per 100 PYO, respectively (27,28). This might be the same socioeconomic status between these countries.…”
Section: Discussionsupporting
confidence: 92%
“…The pooled TB incidence among HIV infected patients of this study revealed that 4.76 (95% CI; 3.69-5.83) per 100 PYO which was in line with the primary studies done in India in 2019, and Tanzania in 2015 which were 4.39 cases, and 4.4 cases per 100 PYO, respectively (27,28). The current finding of pooled incidence was higher than studies conducted in higher-income countries in 2012, in Asia in 2019, in Brazil, Nigeria in 2017 and South Africa 2005 which were 0.3, 0.99, 1.90 and 0.57 and 2.44 per 100 person-years, respectively (29)(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we found higher TB incidence among males compared to females. In general, males show an increased TB prevalence compared with females [ 13 , 14 ], and some studies have also shown that male sex is associated with a higher risk of TB incidence among PLHIV, independent of any ART regimen [ 15 ]. Even though in our study the adjusted analysis did not show a major association between male sex and higher TB incidence, there was a strong association between male sex and lower CD4 cell count at diagnosis.…”
Section: Discussionmentioning
confidence: 99%